2008
DOI: 10.4314/gjpas.v14i3.16819
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Protection In Glucose-6-Phosphate Dehydrogenase Deficient Individuals In Bamenda Population Of Cameroon

Abstract: The high frequency of glucose-6-phosphate dehydrogenase (G6PD) deficiency gene in malaria endemic regions is believed to be due to the enzyme deficiency advantage against fatal malaria. However, the mechanism of this protection is not well understood and therefore was investigated by comparing differences in plasmodial parasitaemia, full blood count profile and the severity of clinical malarial symptoms of G6PD deficient and G6PD non-deficient cohort groups in the population. Our results showed that 10.4% (63/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, nine studies whose data either cannot be extracted, overlapped, or combined with the rest of the data, and thus were excluded. Among the 30 included studies, the species of Plasmodium are only Plasmodium falciparum in 17 studies3571011181920212223242526272829, only Plasmodium vivax in one study30, and combined species ( P. falciparum with P. vivax, P. falciparum with P. malariae, P. vivax with P. malariae , and P. falciparum with P. vivax and P. malariae ) in eight studies1415313233343536. Jalloh 200432, Tantular 199936, and Kruatrachue 196215 reported separate data for P. vivax which meta-analyzed with that of Leslie 201030.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, nine studies whose data either cannot be extracted, overlapped, or combined with the rest of the data, and thus were excluded. Among the 30 included studies, the species of Plasmodium are only Plasmodium falciparum in 17 studies3571011181920212223242526272829, only Plasmodium vivax in one study30, and combined species ( P. falciparum with P. vivax, P. falciparum with P. malariae, P. vivax with P. malariae , and P. falciparum with P. vivax and P. malariae ) in eight studies1415313233343536. Jalloh 200432, Tantular 199936, and Kruatrachue 196215 reported separate data for P. vivax which meta-analyzed with that of Leslie 201030.…”
Section: Resultsmentioning
confidence: 99%
“…Although circumstantial evidence accumulated to support the hypothesis that G6PD deficiency is protective against severe fatal malaria1789; there have been several arguments for7101112 and against131415. Some researchers also argued that perhaps malaria may not be the only factor affecting the deficiency gene locus16.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ruwenda et al and Nguetse et al showed that G6PD deficient males and heterozygous females were less susceptible to severe malaria [10, 22]. A similar phenomenon was observed in Cameroon with G6PD deficient participants having reduced parasitaemia, lower severity of anaemia and malaria symptoms and higher haemoglobin compared to the non-deficient individuals [24]. Nevertheless, G6PD deficiency in Kenya and Tanzania was reported to protect only heterozygous females against severe malaria [29, 30], whereas in Mali it protected only hemizygous males against severe malaria [31].…”
Section: Discussionmentioning
confidence: 80%